101 dalmatians - Bobowicz, Pamela; Disney Enterprises (1996-); Disney Storybook Artists; Random House Children's Books (New York Random House, 2015)
Lots of puppies get lost. How will they get home?
At head of title: Disney 101 dalmatians
English stories
2 13 23
Keywords: Dalmatians -- Juvenile fiction; Dogs -- Juvenile fiction; Puppies -- Juvenile fiction